Life course indices for social determinants of self-rated health trajectory in Korean elderly. (May 2017) - Lee, Jiae; Cho, Sung-Il; Chun, Heeran; Jung-Choi, Kyunghee; Kang, Minah; Jang, Soong-Nang
Highlights: Under-nutrition in childhood results in lower self-rated health in later life. SEP variables on the life course should be measured and monitored. The initial value of health status should be considered for making public health policies. Different health trajectories requires different approaches to health promotion. Abstract: Objectives: This study investigated the self-rated health trajectories of the Korean older population and revealed life-course factors that affect the trajectories over the life course. Methods: Around 1000 older adults were randomly allocated by stratified multi-stage sampling based on the population census, and underwent face-to-face interviews. Self-rated health status, socioeconomic variables over the life course, and demographic variables were included in the analysis. A group-based trajectory model was used to investigate the association between self-rated health and explanatory variables. Results: The enrolled men and women were divided into three groups by trajectory analysis, which showed marked differences in self-rated health trajectories from childhood to senescence. Among older men, those who experienced skipping meals in childhood and those with chronic disease conditions were more likely to be in the lower trajectory groups. Compared to the older men, the likelihood of being in the lower trajectory groups in older women was increased by experience of skipping meals, lower household income, housekeeping labor, receiving Basic Livelihood Security and chronic disease conditions. Conclusion: Various self-rated health trajectories of the Korean older population were identified, and differed according to socioeconomic variables during their life course. Therefore, socioeconomic variables during the life course should be monitored, and health policies directed at the elderly should focus on initial health status from the perspective of a life-course approach.